Addressing Metabolic Dysfunction-Associated Steatohepatitis (Mash) Through Panchakarma: An Evidence-Based Review (AYUSHDHARA, 2025)
Metabolic dysfunction-associated steatohepatitis (MASH, formerly NASH) is an inflammatory progressive liver disease that arises from metabolic dysfunction and hepatic steatosis, carrying risk of fibrosis, cirrhosis, and hepatocellular carcinoma. Lifestyle change is first-line prevention, but complementary approaches such as Ayurvedic Panchakarma, a system of individualized detoxification and rejuvenation therapies are increasingly investigated for prevention and early management of steatotic liver disease. This review synthesizes current understanding of MASH, maps it to Ayurvedic pathogenesis, reviews the putative mechanisms and available clinical/experimental evidence for Panchakarma, and proposes a pragmatic framework for integrating Panchakarma into prevention strategies while highlighting research gaps and safety considerations.